Indeterminacy with preferences featuring multiplicative habits in consumption - Aleksandar Vasilev (Economics and Econometrics Research Institute (EERI), 2019)
We introduce consumption habits into an exogenous growth model augmented with a detailed government sector, and calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2016). We show that in contrast to the case without habits, e.g., Vasilev (2009), when the economy features saddle-path stability, the habit motive alone leads to equilibrium indeterminacy in the model. When habits enter multiplicatively in the representative agent's utility function, the setup exhibits "sink" dynamics, and equilibrium paths are determined by "animal spirits". These results are in line with the findings in the literature, e.g., Benhabib and Farmer (1994, 1996) and Farmer (1999), and have major implications for polcy-making and welfare.
Keywords: E32; E22; E37; 330; Equilibrium indeterminacy; animal spirits; multiplicative consumption habits; Bulgaria